Psychological Well-being Description on Schizoprenia Patients Family Caregiver in Grha Atmas Outpatients Centre Care Bandung - Efri Widianti; Fatimah Qudwatunnisa; Ahmad Yamin (NurseLine Journal, 2018)
Generally, people with schizophrenia are unable to perform individual daily care, they need the assistance of other people to meet their daily needs. Family caregivers who provide sustainable care can feel the stress and depression which were gained during providing sustainable care on schizophrenia patient that can affect their psychological well-being. The purpose of this study was to identify psychological well-being of family caregiver on schizophrenia patients. The result showed that the level of family caregiver’s psychological well-being was in the medium category with percentage as much as 84.9% of respondents. Dimensions that include in moderate category were mostly found in dimension of environmental mastery (87.2%), then followed by dimensions of positive relationship with others (86%), autonomy dimension (84.9%), personal growth and self-acceptance dimension (83.7%) and purpose in life dimension (82.6%). The level of psychological well-being of family caregiver with schizophrenia patients who are undergoing treatment in Outpatient Installation at Grha Atma, Bandung was in moderate category. It is recommended for psychiatric and mental health community nurses to improve the spirituality of family caregiver and provide psychoeducation to family caregiver.